The Expected Role of Remote Sensing Data in the national Development (Ghana): A General Appraisal. (Journal of Science and Technology, 2015)
The effective application of satellite remote sensing data as general data base for national development of resources started in the developed countries after the launching of the ERTS series (now Landsat series) in the early 1970s.The paper highlights possible areas where such data could be applied for the optimum utilization of both renewable and non- renewable natural resources in Ghana. A case study of the practical application of the remote sensing data in the fields of geology, hydrology and forestry is made to illustrate the immense potential of this new tool for the collection of data for national development.